Preparation of surfactant-stabilized gold nanoparticle-peptide nucleic acid conjugates - Duy, Janice; Connell, Laurie B.; Eck, Wolfgang; Collins, Scott D.; Smith, Rosemary L. (Journal of nanoparticle research, 2010)
A simple, two-step method of producing stable and functional peptide nucleic acid (PNA)-conjugated gold nanoparticles using a surfactant stabilization step is presented. PNA are DNA analogs with superior chemical stability and target discrimination, but their use in metallic nanoparticle systems has been limited by the difficulty of producing stable colloids of nanoparticle-PNA conjugates. In this work, the nonionic surfactant Tween 20 (polyoxyethylene (20) sorbitan monolaurate) was used to sterically shield gold surfaces prior to the addition of thiolated PNA, producing conjugates which remain dispersed in solution and retain the ability to hybridize to complementary nucleic acid sequences. The conjugates were characterized using transmission electron microscopy, dynamic light scattering, and UV-visible absorbance spectroscopy. PNA attachment to gold nanoparticles was confirmed with an enzyme-linked immunoassay, while the ability of nanoparticle-bound PNA to hybridize to its complement was demonstrated using labeled DNA.
Gesehen am 20.02.2023